First record of dot-winged crake, Porzana spiloptera, durnford, 1877 (Rallidae) for the central Andes in Argentina - Zarco, Agustín (2017)
Porzana spiloptera, the Dot-wing Crake, has a patchy distribution in southern South America and has previously been considered as inhabiting exclusively lowland wetlands. Here we present evidence of a new population inhabiting a high-elevation site in the Central Andes of Argentina. This record suggests not only a broader distribution but greater tolerance of the species to higher elevation and lower temperatures than has previously been assumed.